Ultrasonographic features of the regressing yolk sac of normal captive Brown kiwi chicks (Apteryx mantelli) vary with age. - Short E; Owen M; Vallee E; Bolwell C; Morgan KJ (John Wiley and Sons, Inc., 2023)
Brown kiwi (Apteryx mantelli) are a culturally significant ratite species endemic to New Zealand. Chicks can develop diseases of the yolk sac which can be fatal if not promptly recognized and treated. Ultrasound examination of the yolk sac is an important component in the evaluation of chicks with suspected yolk sac disease. However, there are currently no reports of the normal ultrasonographic appearance of the regressing yolk sac in this species. The objective of this prospective reference interval study was to describe the normal ultrasonographic appearance of the yolk sac in brown kiwi chicks. Focused coelomic sonographic examinations were performed on 29 healthy chicks from >1 day of age until the yolk sac was completely absorbed or was <1 mL in volume. 41.6% (57/137) of yolks were round/ovoid in shape and 58.6% (80/137) had lobulated margins with invaginations. All yolks (137/137) were hyperechoic relative to adjacent coelomic structures. The heterogeneity of the echogenicity of the yolk was significantly associated with age (increased heterogeneity in younger birds) and was homogeneous, mildly heterogeneous, and moderately heterogeneous in 33% (46/138), 46% (63/138), and 21% (29/138) of all examinations respectively. Intrasac anechoic pockets were seen in 14% (20/139) of yolk sacs. The rate of yolk sac resorption slowed with age. In all examinations identifying a completely absorbed yolk sac or a yolk sac <1 mL in volume, chicks were less than 21 days old. The results of this study provide a reference of normal for the sonographic appearance of the yolk sac in captive brown kiwi chicks.
Keywords: anatomy; avian; coelom; regression; ultrasound; Animals; Yolk Sac; Prospective Studies; Physical Examination